Efeito tipo-anticompulsivo agudo da Ketamina : envolvimento do córtex orbitofrontal e dos receptores AMPA - Tosta, Cristina Luz (2018)
Previous clinical and pre-clinical studies suggest the involvement of orbitofrontal cortex (OFC) and glutamatergic neurotransmission in obsessive-compulsive disorder (OCD). Ketamine, a non-competitive NMDA glutamatergic receptor antagonist, has shown a rapid and long lasting antidepressant effect. The antidepressant effect of ketamine seems to be mediated not only by directly blockade of NMDA receptors, but also by activation of AMPA glutamatergic receptors, increase in extracellular serotonin (5-HT) levels linked to activation of 5-HT1A receptors, and reduction of nitric oxide (NO) synthesis associated to inhibition of nitric oxide synthase (NOS). Ketamine also seems to have rapid anti-obsessive and anti-compulsive effects in clinical and pre-clinical studies. However, there are not studies published so far investigating the mechanisms responsible for this effect of ketamine. Thus, we assessed whether the anticompulsive-like effect of S-ketamine in mice exposed to the marble-burying test (MBT) involves the OFC and depends on activation of AMPA receptors, facilitation of serotonergic neurotransmission and inhibition of nitrergic pathway. Results showed that systemic (10 mg/kg) and intra-OFC (10 nmol/0.1 μl/side) administration of Sketamine reduces marble burying behavior without affecting spontaneous locomotor activity, suggesting an acute anti-compulsive-like effect. In addition, pre-treatment with NBQX (3 mg/kg; AMPA receptor antagonist) blocked the anti-compulsive-like effect of S-ketamine. However, pre-treatment with p-CPA (150 mg/kg/day; 5-HT synthesis inhibitor), WAY100635 (3 mg/kg; 5-HT1A receptor antagonist), or L-arginine (500 mg/kg; nitric oxide precursor) did not counteract S-ketamine effect in the MBT. Moreover, associating sub-effective doses of L-NAME (10 mg/kg; NOS inhibitor) and S-ketamine (3 mg/kg), which did not induce any per se effect, promoted an anticompulsive-like effect. In conclusion, the anti-compulsive-like effect of S-ketamine appears to be a result of its action on OFC, depends on activation of AMPA receptors and also seems to involve the nitrergic pathway